Annotation for the semantic web - Handschuh, Siegfried; Staab, Steffen (Frontiers in artificial intelligence and applications, 2003)
A core technology for making the semantic web happen is the field of semantic annotation, which turns human-understandable content into a machine understandable form. This book reports on the range of technologies that are used to achieve this translation and nourish third millennium applications.